DIGITAL CAPABILITY AND DATA-DRIVEN DECISION MAKING IN MSMEs: A CONCEPTUAL FRAMEWORK FOR ADAPTIVE PERFORMANCE - Nia Riana; Ucu Supriatna (Organisasi Kreatif Indonesia Emas, 2024)
This conceptual article examines digital capability as a capability for strengthening MSME adaptation and sustainable performance. It integrates established perspectives on resources, dynamic capabilities, organizational learning, networks, and entrepreneurial ecosystems. The manuscript does not claim primary survey, interview, experimental, or statistical data. The synthesis develops a staged framework that connects diagnosis, capability building, implementation, evaluation, and learning. It argues that MSMEs create stronger outcomes when managerial routines convert information and relationships into repeatable decisions rather than treating individual programs or technologies as isolated solutions. The framework identifies practical governance requirements, risks, and propositions for future empirical testing.